2012
DOI: 10.3390/ijms131216544
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics and Antioxidant Activity of Mulberry Leaves Depend on Cultivar and Harvest Month in Southern China

Abstract: To elucidate the effects of cultivar and harvest month on the phenolic content and antioxidant activity of mulberry leaves, four major phenolics, including chlorogenic acid (ChA), benzoic acid (BeA), rutin (Rut) and astragalin (Ast), were quantified using an HPLC-UV method. Leaves from six mulberry cultivars, collected from April to October, were analyzed. The antioxidant activity of mulberry leaves was assessed by ferric reducing antioxidant power (FRAP), hydroxyl radical scavenging activity (HSA) and superox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
55
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 17 publications
17
55
1
Order By: Relevance
“…As we know, V C is a standard antioxidant, which could be utilized for evaluating the antioxidant of MLs extract. These results were in agreement with those reported by [21], who indicated the phenolic and antioxidant activity from mulberry leaves. After SG treatment, the reducing capacities were also obviously improved for different SG powder as shown in Fig.…”
Section: Effect Of Sg On Alkaloids Contentssupporting
confidence: 83%
See 2 more Smart Citations
“…As we know, V C is a standard antioxidant, which could be utilized for evaluating the antioxidant of MLs extract. These results were in agreement with those reported by [21], who indicated the phenolic and antioxidant activity from mulberry leaves. After SG treatment, the reducing capacities were also obviously improved for different SG powder as shown in Fig.…”
Section: Effect Of Sg On Alkaloids Contentssupporting
confidence: 83%
“…The antioxidant activity obtained by using HSA radical of MLs varied considerably. Our present result was in agreement with the report published [21], who also investigated the antioxidant from MLs and the results were from 50.9±8.6 to 72.8±6.8%. Moreover, Bruno et al also reported the value of HSA radical scavenging from mulberry [41].…”
Section: Effect Of Sg On the Antioxidant Activity Analyzed Bysupporting
confidence: 83%
See 1 more Smart Citation
“…The quercetin glycosides and free quercetin in buckwheat flowers, leaves, stems, and achenes were discovered by Dadakova in 2010. Plant polyphenol content is influenced by many factors such as variety, location, harvest month and others (Zou et al, 2012;Gunaratne et al, 2013;Zhang et al, 2013). Meanwhile, the phenolic contents may vary in different tissues (Pugliese et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Maybe these differences between the cultivars are associated with a genetic effect of cultivar. Zou et al (2012) reported that genotype and growing environment can affect phytochemical production in an interactive manner. Since all the samples were collected from the same orchard, the differences could not be ascribed to growing location, environment or agricultural practice.…”
Section: Flavonoidsmentioning
confidence: 99%